Developing religious attitude instruments for elementary students - Amsiyah Amsiyah; Felestin Felestin; Noor Faridha (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims: (a) to develop an instrument for assessing the religious attitudes of elementary school students, and (b) to find out the results of the assessment of religious attitudes conducted on students using the instruments that have been made. This research is development research. Data analysis was carried out by proving content validity, construct validity and reliability. The results of the study: (a) the construction of religious assessment instruments includes indicators of worship obedience, gratitude behavior, praying before and after carrying out activities and tolerance in worship, (b) the results of proving content validity are 0.748, the KMO value of the last factor analysis is 0.853 with a significance of 0, 00, the proof of construct validity reduces the data twice in a limited trial and an expanded trial, from the initial number of items as many as 20 items and at the end 19 items in the final instrument which can form 6 new factors, the Cronbach Alpha reliability index is 0.908 which means the instrument is reliable, (c) the dissemination of the religious attitude assessment instrument was carried out with the subject of elementary school students in Wadaslintang District, the results showed that in general the religious attitudes of elementary school students in Wadaslintang District 22.86% belonged to the